2021
DOI: 10.1002/jcph.1962
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lasmiditan for Acute Treatment of Migraine in Adults: A Meta‐Analysis

Abstract: Monotherapy with triptans in acute migraine is ineffective in many patients and contraindicated in certain cardiovascular diseases where alternative therapeutic options are necessary to explore. This meta‐analysis has evaluated the efficacy and safety of lasmiditan for the treatment of acute migraine in adults. After performing a literature search on MEDLINE/PubMed, Scopus, Cochrane databases, and International Clinical Trial Registry Platform, reviewers assessed eligibility and extracted data from 4 relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Somnolence, fatigue, nausea, and paresthesia were also experienced by 3% to 6% of patients in the active arm versus 1% to 2% in the placebo arm. Safety evaluations showed that driving was impaired after lasmiditan use at all doses, and patients reported more sedation at 8 hours after lasmiditan use compared with placebo 32,33 . Patients should therefore be counseled to avoid any activity requiring alertness, including driving, for at least 8 hours after taking lasmiditan.…”
Section: Acute Treatment Options For Migrainementioning
confidence: 99%
“…Somnolence, fatigue, nausea, and paresthesia were also experienced by 3% to 6% of patients in the active arm versus 1% to 2% in the placebo arm. Safety evaluations showed that driving was impaired after lasmiditan use at all doses, and patients reported more sedation at 8 hours after lasmiditan use compared with placebo 32,33 . Patients should therefore be counseled to avoid any activity requiring alertness, including driving, for at least 8 hours after taking lasmiditan.…”
Section: Acute Treatment Options For Migrainementioning
confidence: 99%
“…Because of lasmiditan's unique mechanism of action, headache providers have been eager to define its role in the care of patients with migraine. Several meta-analyses have been published based on data from the previously mentioned clinical trials which have demonstrated that lasmiditan is effective at relieving acute migraine pain compared with placebo [47][48][49] with several demonstrating that the 200 mg dose is more effective than the 100 mg dose. [50][51][52] When compared to triptans, lasmiditan has shown lower odds ratios for pain freedom at 2 hours compared with most triptans (OR 1.72, 95% CI 1.06-2.80 to OR 3.40 95% CI 2.12-5.44) as well as pain relief at 2 hours (OR 1.46, 95% CI 1.09-1.96 to OR 3.31, 95% CI 2.41-4.55).…”
Section: Lasmiditan and Acute Treatment Of Migraine: Place In Therapymentioning
confidence: 99%